2015
DOI: 10.1103/physrevb.92.201201
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic coherent writing of a long-lived semiconductor spin qubit using one ultrafast optical pulse

Abstract: We use one single, few-picosecond-long, variably polarized laser pulse to deterministically write any selected spin state of a quantum dot confined dark exciton whose life and coherence time are six and five orders of magnitude longer than the laser pulse duration, respectively. The pulse is tuned to an absorption resonance of an excited dark exciton state, which acquires non-negligible oscillator strength due to residual mixing with bright exciton states. We obtain a high fidelity one-to-one mapping from any … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 36 publications
3
32
0
Order By: Relevance
“…Dark exciton. Dark excitons are nowadays considered as important platform for various quantum-dot applications [70][71][72][83][84][85][86][87][88] . In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dark exciton. Dark excitons are nowadays considered as important platform for various quantum-dot applications [70][71][72][83][84][85][86][87][88] . In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we study dark-exciton spectra 15 , 70 72 , properties of which in quantum dashes, such as the non-zero optical activity 63 , 73 and splitting, appear to be dominated by shape deformation and rather immune to alloying effects.…”
Section: Introductionmentioning
confidence: 99%
“…1c. The conduction-band electron [1,2,27], the valenceband hole [28,29], and the dark exciton (DE-optically inactive electron-hole pair) [30][31][32] are long-lived ground electronic spin qubits in a QD system. The first two are Kramers' degenerate, but the third one is not.…”
Section: Introductionmentioning
confidence: 99%
“…DEs, like BEs, are neutral and therefore have a long spin coherence time 16 . Recently, it was demonstrated that the DE can be optically initiated in a coherent state by an ultrashort resonant optical pulse 17 , and that its quantum state can be coherently controlled and reset using short optical pulses 16,18 , making it thus an attractive matter spin qubit.…”
mentioning
confidence: 99%